2010
DOI: 10.1128/aac.00343-09
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Pharmacokinetics of Urtoxazumab, a Humanized Monoclonal Antibody, against Shiga-Like Toxin 2 in Healthy Adults and in Pediatric Patients Infected with Shiga-Like Toxin-Producing Escherichia coli

Abstract: Shiga-like toxin-producing Escherichia coli (STEC) infection causes diarrhea, which is often bloody and which can result in potentially life-threatening hemolytic-uremic syndrome (HUS). Urtoxazumab, a humanized monoclonal antibody directed against the Shiga-like toxin 2 (Stx2) produced by STEC, has been developed as a promising agent for the prevention of HUS. Single randomized, intravenous, double-blind, placebo-controlled doses of urtoxazumab were administered to assess its safety and pharmacokinetics in hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
76
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 20 publications
1
76
0
1
Order By: Relevance
“…With this in mind, we developed HuMAbs to neutralize Stx (17)(18)(19), which were shown to be highly effective in protecting STEC-infected piglets (17,20,21). Other investigators have also developed Stx-neutralizing chimeric (47) or humanized (48,49) MAbs. HuMAb 5C12, specific for Stx2, was found to be highly effective in protecting piglets 48 h after STEC infection; a dose of 0.4 mg/kg of body weight protected 80% of piglets (20).…”
Section: Discussionmentioning
confidence: 99%
“…With this in mind, we developed HuMAbs to neutralize Stx (17)(18)(19), which were shown to be highly effective in protecting STEC-infected piglets (17,20,21). Other investigators have also developed Stx-neutralizing chimeric (47) or humanized (48,49) MAbs. HuMAb 5C12, specific for Stx2, was found to be highly effective in protecting piglets 48 h after STEC infection; a dose of 0.4 mg/kg of body weight protected 80% of piglets (20).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is only one anti-infective MAb currently approved for use in humans, there are other MAbs targeting pathogens being tested in human clinical trials (21,23,25,37). These anti-infective MAbs, which are specific for pathogen and not human antigens, are anticipated to have relatively few off-target toxicities.…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal antibodies (MAbs) have been shown to reduce the cytotoxicity of Stx1 and Stx2 in vitro (381), while Urtoxazumab, a humanized MAb against Stx2, was shown to be safe in a phase 1 study (382). Similarly, phase 1 clinical trials of chimeric monoclonal Stx1-and Stx2-neutralizing antibodies were also shown to be generally well tolerated in injected volunteers (383,384).…”
Section: Clinical Considerationsmentioning
confidence: 99%